Identification of New Ethanol-Tolerant Yeast Strains with Fermentation Potential from Central Patagonia - Cubillos-Riffo, F; Quintrel-Poblete, P; Villarreal-Diaz, P (John Wiley and Sons Ltd, 2022)
The quest for new wild yeasts has increasingly gained attention because of their potential ability to provide unique organoleptic characters to fermented beverages. In this sense, Patagonia offers a wide diversity of ethanol-tolerant yeasts and stands out as a bioprospecting alternative. This study characterized the genetic and phenotypic diversity of yeast isolates obtained from Central Chilean Patagonia and analyzed their fermentation potential under different fermentative conditions. We recovered 125 colonies from Nothofagus spp. bark samples belonging to five yeast species: Saccharomyces eubayanus, Saccharomyces uvarum, Lachancea cidri, Kregervanrija delftensis, and Hanseniaspora valbyensis. High-throughput microcultivation assays demonstrated the extensive phenotypic diversity among Patagonian isolates, where Saccharomyces spp and L. cidri isolates exhibited the most outstanding fitness scores across the conditions tested. Fermentation performance assays under wine, mead, and beer conditions demonstrated the specific potential of the different species for each particular beverage. Saccharomyces spp. were the only isolates able to ferment beer wort. Interestingly, we found that L. cidri is a novel candidate species to ferment wine and mead, exceeding the fermentation capacity of a commercial strain. Unlike commercial strains, we found that L. cidri does not require nutritional supplements for efficient mead fermentation. In addition, L. cidri produces succinic and acetic acids, providing a distinct profile to the final fermented product. This work demonstrates the importance of bioprospecting efforts in Patagonia to isolate novel wild yeast strains with extraordinary biotechnological potential for the fermentation industry. © 2021 John Wiley & Sons, Ltd.